$$\int\sin^4(x)\cos^2(x)\space\text{d}x=$$ $$\int\sin^4(x)\left(1-\sin^2(x)\right)\space\text{d}x=$$ $$\int\left(\sin^4(x)-\sin^6(x)\right)\space\text{d}x=$$ $$\int\sin^4(x)\space\text{d}x-\int\sin^6(x)\space\text{d}x=$$
Tienes que usar el doble de la fórmula de reducción:
$$\int\sin^m(x)\space\text{d}x=-\frac{\cos(x)\sin^{m-1}(x)}{m}+\frac{m-1}{m}\int\sin^{m-2}(x)\space\text{d}x$$
$$\frac{\sin^5(x)\cos(x)}{6}+\frac{1}{6}\int\sin^4(x)\space\text{d}x=$$ $$\frac{\cos(x)\sin^3(x)\left(4\sin^2(x)-1\right)}{24}+\frac{1}{8}\int\sin^2(x)\space\text{d}x=$$ $$\frac{\cos(x)\sin^3(x)\left(4\sin^2(x)-1\right)}{24}+\frac{1}{8}\int\left[\frac{1}{2}-\frac{\cos(2x)}{2}\right]\space\text{d}x=$$ $$\frac{\cos(x)\sin^3(x)\left(4\sin^2(x)-1\right)}{24}+\frac{1}{8}\left[\frac{1}{2}\int1\space\text{d}x-\frac{1}{2}\int\cos(2x)\space\text{d}x\right]=$$ $$\frac{\cos(x)\sin^3(x)\left(4\sin^2(x)-1\right)}{24}+\frac{1}{8}\left[\frac{x}{2}-\frac{1}{2}\int\cos(2x)\space\text{d}x\right]=$$
Sustituir $u=2x$ y $\text{d}u=2\space\text{d}x$ :
$$\frac{\cos(x)\sin^3(x)\left(4\sin^2(x)-1\right)}{24}+\frac{1}{8}\left[\frac{x}{2}-\frac{1}{2}\int\cos(u)\space\text{d}u\right]=$$ $$\frac{\cos(x)\sin^3(x)\left(4\sin^2(x)-1\right)}{24}+\frac{1}{8}\left[\frac{x}{2}-\frac{1}{2}\int\cos(u)\space\text{d}u\right]=$$ $$\frac{\cos(x)\sin^3(x)\left(4\sin^2(x)-1\right)}{24}+\frac{1}{8}\left[\frac{x}{2}-\frac{\sin(u)}{4}\right]+\text{C}=$$ $$\frac{\cos(x)\sin^3(x)\left(4\sin^2(x)-1\right)}{24}+\frac{1}{8}\left[\frac{x}{2}-\frac{\sin(2x)}{4}\right]+\text{C}$$